Are Sensory-Motor Relationships Encoded ad hoc or by Default?: An ERP Study - Morera, Yurena; van der Meij, Maartje; de Vega, Manuel; Barber, Horacio A. (Frontiers in Psychology, 2019)
In this event-related potentials study we tested whether sensory-motor relations between concrete words are encoded by default or only under explicit ad hoc instructions. In Exp. 1, participants were explicitly asked to encode sensory-motor relations (e.g., “do the following objects fit in a pencil-cup?”), while other possible semantic relations remained implicit. In Exp. 2, using the same materials other group of participants were explicitly asked to encode semantic relations (e.g., “are the following objects related to a pencil-cup?”), and the possible sensory-motor relations remained implicit. The N400 component was sensitive to semantic relations (e.g., ‘desk’ related to 'pencil-cup') both under implicit (Exp. 1) and explicit instructions (Exp. 2). By contrast, most sensory-motor relations (e.g., ‘pea’ fitting in ‘pencil-cup’) were encoded ad hoc under explicit instructions (Exp.1). Interestingly some sensory-motor relations were also encoded implicitly, but only when they corresponded to “functional” actions associated with high-related objects (e.g., ‘eraser’ fitting in ‘pencil-cup’) and occurring at a late time window (500-650 ms; Exp. 2), suggesting that this type of sensory-motor relations were encoding by default.